The social stigma of the released prisoner: A field study on a sample of prisoners released in the state of Jijel - BOUKALMOUNE, Daoud (Journal of Human Sciences, 2020)
Crime is a social phenomenon that exists in all societies and has a natural connection, because it relates to the structures of society itself and the nature, complexity and development of social life. Social theories have been concerned with the study and interpretation of the most important reasons leading to the criminal behavior of the individual. Among these theories is the theory of social stigmatization which stems from the first two Muslims: Deviation is a relative phenomenon that is not consistent in getting out of tolerant boundaries which causes society to reject this unacceptable behavior and thus stigmatize The second is that deviation does not originate from a single source, but rather as a result of a set of situations and circumstances. It is a social process that takes place between two parties: the deviant act of the delinquent and the reaction of others to this deviation.